2005
DOI: 10.1111/j.1365-201x.2005.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic characterization of stress‐induced myocardial infarction in atherosclerotic mice

Abstract: This is the first mouse model showing that increased STU-area variability is indicative of MI development in atherosclerotic mice following ischaemic stress. Furthermore, our findings suggest a two-phase pathway for the infarction development: an initial phase comprising a transient ischaemic response which triggers a delayed second phase of ischaemia and MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Epidemiologic evidence supports the idea that stress, which can activate the sympathetic nervous system, is a risk factor for acute cardiovascular events (10,40). Hemdahl et al (17) reported that both stress and hypoxic stimulation could trigger myocardial infarction in apoE Ϫ/Ϫ /LDLR Ϫ/Ϫ mice. In the present study, stress acted as an ideal physiological trigger instead of pharmacological triggers to induce plaque disruption.…”
Section: Discussionmentioning
confidence: 92%
“…Epidemiologic evidence supports the idea that stress, which can activate the sympathetic nervous system, is a risk factor for acute cardiovascular events (10,40). Hemdahl et al (17) reported that both stress and hypoxic stimulation could trigger myocardial infarction in apoE Ϫ/Ϫ /LDLR Ϫ/Ϫ mice. In the present study, stress acted as an ideal physiological trigger instead of pharmacological triggers to induce plaque disruption.…”
Section: Discussionmentioning
confidence: 92%
“…The goal of the current study was to characterize the influence of sex and age on heart protein expression. Due to the scarcity of human tissue samples, we first employed C57BL/6 mice, a standard mouse strain that has been proven to be a pertinent model for studying human heart diseases (17,18). The use of well-characterized inbred mouse strains reduces the possible influences of genetic polymorphisms on protein expression patterns, a problem involved in investigations of human individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Male ApoE (Ϫ͞Ϫ) mice and ApoE (Ϫ͞Ϫ) ϫ LDLR (Ϫ͞Ϫ) mice on the C57BL͞6J background were obtained from Malling Beck (Ry, Denmark) after they were weaned. The ApoE (Ϫ͞Ϫ) ϫ LDLR (Ϫ͞Ϫ) mice were fed a Western-type diet containing cornstarch, glucose, sucrose, cocoa butter, cellulose, minerals, vitamin mix, 0.15% cholesterol, and 21% total fat (wt͞wt) for 8 months (24). The ApoE (Ϫ͞Ϫ) mice were fed standard chow for 25 weeks.…”
Section: Methodsmentioning
confidence: 99%